Energy Efficient Microwave Irradiation of Sago Bark Waste (SBW) for Bioethanol Production - Saravana, Kannan Thangavelu; Abu Saleh, Ahmed; Ani, F.N. (Trans Tech Publications, 2013)
The energy efficiency of microwave irradiation for bioethanol production from sago bark waste (SBW) was studied. The maximum sugar yield of 62.6 % was reached at the biomass loading 20% (w/w). The high ethanol yield of 60.2% theoretical yield, ethanol concentration 30.67 g/l was achieved by diluted sulfuric acid supported microwave irradiation with 40% (w/w) biomass loading at 60 h fermentation. The energy consumption of microwave irradiation to produce 1 g sugar and 1 g ethanol was calculated separately. The lowest energy consumption was noticed while biomass loading and energy input were fixed at 40 % (w/w) and 33 kJ (1100 W for 30 s) respectively, and it is amounted to 1.27 and 1.76 kJ to produce 1 g of sugar after enzymatic hydrolysis and 1 g ethanol after fermentation, individually. Usually, 1 g ethanol can produce approximately 27 kJ of energy, and therefore, the energy input for the microwave pretreatment was only 7% of the energy output. The microwave irradiation technique established for SBW to produce ethanol succeeded in 80% energy savings for producing 1 g ethanol compared to rape straw by microwave pretreatment previously reported.